Cytotoxicity and Genome Characteristics of an Emetic Toxin-Producing Bacillus cereus Group sp. Isolated from Raw Milk - Pheepakpraw, Jintana; Sinchao, Chanita; Sutheeworapong, Sawannee; Sattayawat, Pachara; Panya, Aussara; Tragoolpua, Yingmanee; Chitov, Thararat (Foods, 2025)
The Bacillus cereus group frequently contaminates milk and dairy products. Some members of this group can produce the heat-stable pre-formed toxin cereulide, which causes emetic foodborne intoxication. This study characterised emetic B. cereus group isolates from raw cow’s milk in the biochemical, genetic, and toxigenic aspects. Of the 158 B. cereus group isolates derived from 99 raw milk samples, 7 (4.43%) harboured cereulide synthetase A (cesA), which encodes a cereulide synthetase associated with the emetic phenotype. Heat-treated culture filtrates from the cesA-positive isolates demonstrated cytotoxicity to HepG2 and Caco-2 cells, resulting in cell viabilities of 32.22–36.57% and 44.41–47.08%, respectively. The cytotoxicity levels were comparable to those of the reference emetic strain, F4810/72 (alternately termed AH187). Genome analysis of a representative isolate, CSB98, revealed the complete ces gene cluster with additional virulence factors such as non-haemolytic enterotoxin, haemolysins and phospholipases, suggesting that the isolate could be both emetic and diarrhoeagenic. CSB98 exhibited a closer relationship to the type strain of B. paranthracis than to that of B. cereus sensu stricto (ATCC 14579). The genomes of CSB98 and AH187 were indistinguishable through OrthoANI analysis, but 13 variants were identified via SNP calling. These results affirm genetic conservation among the emetic traits.